Batik Motif Parang Dari Court Art Menuju Global Trend - Rizki Kurniawan (JURNAL RUPA, 2016)
Like other cultures, batik has undergone many developments and changes. Batik Parang in particular has experienced it many times in different periods with a very long time span. From this period, we can see that batik parang have also experienced some ups and downs conditions, which not only caused by outside influences, but also can be caused by various influences from within his own culture. In a due process of change will produce a wide range of output that inevitably will influence directly a form of culture. These conditions also experienced by batik, especially batik parang in the process of developing and adapting to changes. As in batik parang, which evolved from court art, must be degraded into folk art. Batik in order to survive as a cultural form, should be able to adapt changes and sacrificed by decreasing its symbolic meanings to continued its existence in the future.